2008
DOI: 10.3354/meps07274
|View full text |Cite
|
Sign up to set email alerts
|

Quantile regression models for fish recruitment–environment relationships: four case studies

Abstract: Understanding and modelling the environmental control of fish recruitment has been a central question in fish population ecology for the last century. Most environment -recruitment models have primarily been developed to model mean recruitment using conventional regression techniques which assume that all environmental parameters are included and that the residual unexplained variability is unstructured. However, the complexity of environmental controls and the empirical evidence that many relationships have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…Quantile regression has been demonstrated as a useful tool in ecological studies for detecting limiting factors (Cade et al, 1999;Cade and Noon, 2003;Planque and Buffaz, 2008). To understand if a factor is limiting, it is helpful to model the maximum response instead of a mean.…”
Section: Quantile Regression Background and Statistical Methodsmentioning
confidence: 99%
“…Quantile regression has been demonstrated as a useful tool in ecological studies for detecting limiting factors (Cade et al, 1999;Cade and Noon, 2003;Planque and Buffaz, 2008). To understand if a factor is limiting, it is helpful to model the maximum response instead of a mean.…”
Section: Quantile Regression Background and Statistical Methodsmentioning
confidence: 99%
“…In most marine systems and for many fish populations, relationships between environment and recruitment have been proposed, but they have often been contested or have failed when retested with new and longer sets of observations (see Myers, 1998). The multiplicity and complexity of the environmental controls limit our ability to adequately understand and model environmentrecruitment relationships (Planque and Buffaz, 2008). Studies showed that a variety of environmental and oceanographic variables (local scale effects, such was SST) affect the same species (and or species stocks) differently across inter and intra geographical scales (Planque and Frédou, 1999;Ullah et al, 2012;Teixeira et al, 2013).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Factors such as the NAO (albacore, Arregui et al 2006;sardine, Alheit & Hagen 1997; several fish stocks, mammals and seabirds, Hemery et al 2008), EA pattern (anchovy, Borja et al 2008); temperature anomaly (hake, Fernandes et al 2010), upwelling strength (anchovy, Borja et al 2008), turbulence (anchovy, mackerel and hake, Borja et al 1998, Allain et al 2007, Fernandes et al 2010, river discharge (anchovy, Planque & Buffaz 2008) and Ekman transport (anchovy, Irigoien et al 2008) have been shown to have significant effects on the recruitment or abundance of these species.…”
Section: Relationships Between Climate and Fishesmentioning
confidence: 99%